Complex problem solving and organizational psychology: of nomological networks, microworlds, and interdisciplinary dialogue - Neubert, Jonas C. (2017)
The founding fathers of Complex Problem Solving (CPS) research utilized the advent of computer-technology to connect problem solving research to the affordances of everyday life. During the last decades, this tradition has led to a thriving field of CPS research with interesting implications for a number of applied settings. The goal of this thesis is (re-)connecting CPS research to a specific area of application: Organizational Psychology (OP). To this end, the first core paper of the thesis explores the relation of CPS to one of the most important psychological constructs in OP, namely intelligence, thereby complementing the nomological network of the construct (Chapter 2). The second core paper of the thesis is closer aligned with the practical side of utilizing a construct in OP and considers the valid and reliable assessment of CPS with the help of finite state automata (Chapter 3). The third core paper of the thesis builds on this foundation in terms of construct and assessment and explores the connections between CPS and OP in a discussion of researchers and practitioners from both fields (Chapter 4). In summary, the thesis aims at complementing the current state of insights within CPS research in light of an application in OP and the start of an exchange between both domains.